Graduation of Sanctions in the Lawyer's Liability for Misconduct Committed by Non-Lawyers under his or her Supervision - Zubizarreta Rondón, Gloria (2009)
This paper addresses the liability of lawyers for misconduct committed by non-lawyers under their supervision. The author mentions that the commission of misconduct violates the due sponsorship and the due appearance of the profession. Also, since there is no internal regulation on the matter, the author analyzes three sources to support the proposal for the graduation of sanctions: doctrine, jurisprudence and comparative law. Finally, the author stresses the importance of the graduation of sanctions, establishes criteria and presents a table with cases of misdemeanors regulated according to the seriousness of the practice carried out: serious, moderate and minor cases of sanction.